The "places and non-places" held by women in social economy organizations - Parente, Cristina (2018)
Scientific literature and facts have highlighted the perpetuation of gender inequality in the labour market in spite of the ongoing endeavours of political bodies and legal norms to eliminate the vertical and horizontal segregation of women. Portuguese Social Economy Act stresses the respect for the values [] of equality and non-discrimination [], justice and equity []. In this paper, we offer a reflection on indicators that uncover vertical and horizontal segregation in the labour market. Based on a mixed methodological approach, we found very high rates of employment feminization in social economy organizations. Women are mainly allocated to technical and operational activities, being ultimately underrepresented in statutory boards and as such excluded from deliberation and strategic decision. The sector is moving away from the ideals of justice and social equity and may preserve womens non-place in the definition of the public and strategic direction and in the most invisible/private organizational places.